Konseling Cognitive Behavioral dengan Teknik Modelling untuk Meningkatkan Self Abasement - Istiqomah, Nur Aini Putri; Suranata, Kadek; Suarni, Ni Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2018)
This study aims to determine the application of behavioral cognitive counseling with modeling techniques to improve self-abasement students SMP Negeri 3 Singaraja. This type of research is quasi experiment with pretest-posstest control group design. Sampling using purposive sampling technique and obtained 7 students who have low self-abasement. Data collection method used is questionnaire as main data, while observation, interview and diary as supporting data to collect data about self abasement. All data in this research using data logit previously processed through Rasch analysis with help of Winstep application. Data analysis for hypothesis test is done by using t-Burning and t-test. The results showed the application of behavioral cognitive counseling with effective modeling techniques to improve self-Abasement value of tcount> ttable (23,26> 2,440). And there are differences in self-abasement among students who received treatment and who did not receive counseling treatment cognitive behavioral modeling techniques tcount> ttable (8.10> 1.782).Â Keywords: counseling behavioral cognitive, modeling, self abasement